2007
DOI: 10.12968/ijpn.2007.13.12.27886
|View full text |Cite
|
Sign up to set email alerts
|

The paradox of palliative care nursing across cultural boundaries

Abstract: The purpose of this qualitative study, using a modified grounded theory approach, was to investigate how palliative care nurses care for people from cultural backgrounds other than their own. Ten palliative care nurses were interviewed. The semi-structured interviews were tape-recorded and transcribed verbatim. Analysis commenced as soon as data began to emerge. The findings show that palliative nursing across cultural boundaries is paradoxical. In endeavouring to treat everyone equally, nurses treated everyon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Among 21 selected articles, four [50,51,53,54] used the grounded theory approach; one [55] used the modified grounded approach; 11 [52,56,57,59e66] used concept analyses; two [43,67] used both thematic and content analyses; and three [58,68,69] did not specify the types of methods used for theorizing. Among four articles that used the grounded theory methodology, two specified their use of Glaser's methodology [53,54].…”
Section: Various Theorizing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 21 selected articles, four [50,51,53,54] used the grounded theory approach; one [55] used the modified grounded approach; 11 [52,56,57,59e66] used concept analyses; two [43,67] used both thematic and content analyses; and three [58,68,69] did not specify the types of methods used for theorizing. Among four articles that used the grounded theory methodology, two specified their use of Glaser's methodology [53,54].…”
Section: Various Theorizing Methodsmentioning
confidence: 99%
“…For example, the framing sexual risk behavior model was presented with the purpose of exploring the lesser known phenomenon of an urban, adolescent American Indian young female's sexual risk behaviors [54]. Also, the theory of Cross-Cultural Endeavor in Palliative Care Nursing was developed with the purpose of investigating how palliative care nurses care for people from diverse cultural backgrounds [55]. Five (23.8%) studies aimed at defining and clarifying the concepts by using phrases of "to define" [56], "to enhance clarity" [57], or "to present a detailed explanation" [58].…”
Section: Purposes Of Exploring Defining and Clarifying And Reflectingmentioning
confidence: 99%
“…Additionally within palliative care religion and religious beliefs can influence preferences for management of symptoms, sometimes adversely [10]. For example some rreligious beliefs can lead to the rejection of medication to manage symptoms causing practical and ethical challenges for staff [10,11]. In the growing diversity of the ROI, staff face unfamiliar practices and customs which can make them protective of other patients [11] and lead to uncertainty, apprehension, discomfort, and fear of causing offence [12].…”
Section: Introductionmentioning
confidence: 99%
“…For example some rreligious beliefs can lead to the rejection of medication to manage symptoms causing practical and ethical challenges for staff [10,11]. In the growing diversity of the ROI, staff face unfamiliar practices and customs which can make them protective of other patients [11] and lead to uncertainty, apprehension, discomfort, and fear of causing offence [12]. Although the particular spiritual and religious needs of ethnically diverse patients in healthcare in the ROI have received little attention, small localised studies have identified gaps in service provision, with patients leaving the hospital situation feeling distressed because their religious and spiritual needs may not have been met [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation